Kemaritiman Pelaut Mandar dalam Kalindaqdaq (Analisis Trikotomi Semiotika) - Ahmad Akbar (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Maritime Mandar sailor in kalindaqdaq with semiotic trichotomy approach (icon, index, and symbol) by Charles Sanders Peirce.This study aims to determine the maritime icons, indices, and symbols of Mandar seafarers in maritime-themed kalindaqdaq. This type of research uses qualitative methods with applying Pierce's semiotic theory. In this study, the objects to be studied are 10 kalindaqdaq texts. The results of the study conclude that in the Kalindaqdaq Mandar with a maritime theme, there is a very important meaning in the delivery of kalindaqdaq. The meaning contains moral messages, conveys many messages of love, and information about the anatomy of the shape of the boat.